Identitas dan Kebijakan Luar Negeri: Konstruksi Identitas dalam Kebijakan Luar Negeri Tunisia Pasca Revolusi - Ibad, Faizul; Muta’ali, Abdul (Journal Of Middle East and Islamic Studies, 2021)
This study aims to examine the construction of identity in post-revolutionary Tunisian foreign policy. This research is interesting because Tunisia is the only country in the Middle East that has successfully passed the Arab Spring wave and formed a democratic government. While many other Arab countries did not make it through the wave of democratization, some of them even fell into protracted civil conflict. The polarization of Arab countries as a result of the Arab spring has caused fragmentation among other Arab countries. Saudi Arabia and the United Arab Emirates tried to block the revolution because it would threaten the integrity of their monarchy. On the other hand, Qatar and Turkey in every narrative support Arab pro-revolution groups. This polarization will affect Tunisia's foreign policy, especially since only Tunisia managed to pass the Arab spring wave. Based on the pattern of identity formation, due to changes in the domestic structure, the Tunisian revolution has given birth to the Tunisian identity as a democratic country. This study uses the constructivist concept of identity as the theoretical framework. The finding in this study is that Tunisian foreign policy in two different governments (Moncef Marzouki and Beji Caid Essebsi) shows the influence of identity, in which Tunisia considers Qatar and Turkey as friends because they have the same identity. Even though Qatar is not a democracy, its support for the democratization of Tunisia shows a common perception. While relations with Saudi and the United Arab Emirates are conflicting, they even consider the two as enemies. This is because of the difference in identity between Tunisia as a democracy and Saudi Arabia-United Arab Emirates as a monarchy.